ASSESSMENT OF POTATO GROWING POTENTIAL IN UKRAINE DUE TO ZONAL SPECIALIZATION AND RAW MATERIAL SOURCES - Viktor TYMCHUK; Valerii KOLIADA; Olha KOLIADA; Sergii CHUНAEV; Liudmyla OSYPOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper studied the assessment of potato growing potential on organizational and economic bases in Ukraine. The materials presented according to specificity of production rates and conditions from 1940 to 2018. On the basis of the gross potato production indicator in Ukraine for 78 years (from 1940 till the current state), indicators and tendencies of potato growing development are determined. From the standpoint of potential vectors of zonal specialization (ZSP) and standardized raw materials sources (RMS) such realization was investigated. The survey has found, that the main principles of end-to-end coordination in potato growing industry of Ukraine depend on agricultural enterprises and farms input in the short and medium term and on households in the long term perspectives. The data showed that the technologies involved in potato growing still need systemic improvement and development towards convergent ones with the level of realization of the genetic potential of productivity for more than 70%.